INTERDISCIPLINARY ART PRACTICES IN INDIA - Saba, Rafi; Ahmad, Furqan (International Journal of Research -GRANTHAALAYAH, 2016)
Today in this fastest changing world of science, technology, inventions and information technology, every field is connected to one another in some way. Science technology and innovations are affecting almost all the facets of life and disciplines of knowledge hence art is not the exception. Today art is not limited to the paint and canvases instead it has different aspects. This study was conducted, referring to the changes in the art practices and examines some recent developments in contemporary Indian Arts. Interdisciplinary means combining, connecting or involving two or more academic, scientific, or artistic disciplines. It represents the fusion of two or more professions, technologies, departments, or the like.